MOLECULAR CHARACTERISATION OF SOME MULTI-DRUG RESISTANT SALMONELLA ENTERICA OF HUMAN ORIGIN IN SOUTHEAST NIGERIA (2016)
There has been an increase in the occurrence of antibiotic resistance among Salmonella enterica, one of the commonest causative agents of Salmonella infections. Fluoroquinolones and third generation cephalosporins are usually the drugs of choice in the management of Salmonella infections. Previous reports have indicated common occurrence of multi-drug resistance (MDR) including resistance to β-lactams and fluoroquinolones among clinical Gram-negative organisms. However, there is paucity of information on the genetic determinants of resistance to β-lactam and fluoroquinolones from S. enterica in Southeast Nigeria. This study screened for the presence of Extended-Spectrum Beta-Lactamases (ESBL) and mutations in gyrA and parC genes of S. enterica from human origin in the Southeast Nigeria. Twenty-five S. enterica isolates from stool of patients suspected to have Salmonella infection were collected from each of four hospitals (one teaching hospital and three Federal Medical Centres) in Southeast Nigeria between July and September, 2010. The isolates were confirmed using Microbact identification kit®. Antibiogram for the isolates was determined by disc-diffusion based on Clinical and Laboratory Standards Institute breakpoints. Five commonly used antibiotics (amoxicillin-clavulanic acid, cefotaxime, ceftriaxone, ciprofloxacin and levofloxacin) in the treatment of Salmonella infections were selected for determination of Minimum Inhibitory Concentrations (MIC) against the isolates using broth-dilution method. Isolates resistant to two or more different classes of antibiotics were classified as MDR. Isolates resistant to fluoroquinolones and cephalosporins were exposed to mutagens for R-plasmid curing, and ESBL were detected phenotypically using Double-Disk Synergy Test. Genomic and plasmid DNA of mutagen treated and untreated isolates were extracted by boiling and alkaline lysis, respectively. Polymerase chain reaction was used to amplify blaTEM, blaSHV and blaCTX-M among the ESBL positive isolates, and Quinolone Resistance Determining Regions (QRDR) among fluoroquinolone resistant isolates, followed by sequencing of the QRDRs. Antibiogram data were analysed using ANOVA at p = 0.05. The 100 clinical isolates collected were confirmed to be S. enterica. Percentage resistance obtained was: amoxicillin-clavulanic acid (87%), chloramphenicol (80%), amoxicillin (80%), co-trimoxazole (78%), sparfloxacin (78%), streptomycin (77%), gentamicin (51%), ceftazidime (44%), perfloxacin (29%), ciprofloxacin (29%), ofloxacin (28%), cefotaxime (27%), ceftriaxone (22%) and levofloxacin (22%). Eighty of the 100 isolates were MDR and the ranges of MICs of the selected antibiotics were: amoxicillin-clavulanic acid (≥ 50 µg/mL), cefotaxime (6.25 - 25 µg/mL), ceftriaxone (6.25 – 12.5 µg/mL), ciprofloxacin (6.25 – 12.5 µg/mL) and levofloxacin (12.5 - 25 µg/mL). Of the 100 isolates, nine MDR isolates carrying R-plasmid were cured. Thirty six of the MDR isolates produced ESBL phenotypically, of which 13 were blaCTX-M positive. DNA sequencing revealed single point mutations in gyrA at amino acid positions Asp-87-Gly, Asp-87-Asn and Ser-83-Tyr in 55 (68.8%), and double mutation in parC at positions Asp-87-Gly in 14 (17.5%). There was significant difference in the activity of the individual antibiotics against the isolates. The occurrence of mutations in gyrA and parC genes, and chromosomal blaCTX-M were responsible for fluoroquinolones and cephalosporins resistance, respectively in some of the Salmonella enterica from Southeast Nigeria. Hence, alleviating the fear of easy spreading of quinolone and cephalosporin resistant isolates.